Agricultural production in Nepomuceno-MG, Brazil, in the period 1995-2017 - Vilas Boas, Lucas Guedes (Geografares, 2020)
The primary sector, mainly coffee production, has emphasis in the economy of Nepomuceno, which has approximately 27 thousand inhabitants and is located in Sul de Minas planning region. Thus, the objective of the article was to analyze the Nepomuceno’s agricultural production between 1995 and 2017. Document analysis, bibliographic research and fieldwork were the methodological procedures adopted in the study. In the analyzed period, coffee production continued as the predominant agricultural activity in the municipality. Furthermore, there was a great decrease in rice cultivation and soybean culture growth in Nepomuceno. In general, agricultural productivity was increased in the interim studied, mainly due to the dissemination of chemical fertilizers, transgenic seeds and agricultural machinery in municipal agriculture.